Tinjauan Hukum Ekonomi Syariah Tentang Praktek Arisan Uang Yang Di Ganti Dengan Barang (Studi Kasus Di Pasar Pasirwangi Kecamatan Pasirwangi Kab. Garut) - Ai Wati; Afwan, Akmal Hidayat (Jurnal Hukum Ekonomi Syariah, 2022)
In the modern world, various economic activities are conducted by different groups, including "arisan," a traditional rotating savings and credit association commonly practiced in Indonesia. Arisan comes in various models, from monetary arisan to goods-based arisan. The arisan practice observed in Pasirwangi Market, Pasirwangi Sub-District, Garut Regency, caught the attention of the author due to the replacement of money with goods without clear contractual terms, causing dissatisfaction among the members. Based on this issue, the author conducted research on "Sharia Economic Law Perspective on the Practice of Goods-Based Arisan in Place of Monetary Arisan (Case Study at Pasirwangi Market, Pasirwangi Sub-District, Garut Regency)." This research aims to understand the practice of goods-based arisan in Pasirwangi Market from the perspective of Sharia economic law.   The research method employed is field research, with qualitative interviews to directly understand the phenomenon experienced by the research subjects. The arisan activity does not contradict Sharia economic law as it is based on voluntary participation and does not involve prohibited elements. Subsequently, a second negotiation was held among all arisan members, where the arisan leader explained the reasons for replacing monetary arisan with goods to better meet the members' needs. Consequently, all arisan members agreed to change the arisan contract to goods-based. However, after this change, the prices of the goods did not match market prices, leading the arisan leader to increase the prices to allow the surplus money from buyers to be taken by the arisan leader. Although this resulted in losses for the members, they willingly accepted the surplus money taken by the arisan leader, believing it would cover transportation costs.  Keywords: Arisan, Money, Goods, Sharia Economic Law.